Enhancing Production Capacity and Work Ergonomics at Cemilan Wety through the VGC-J300 Slicing Machine and The High-Pressure Stove - Nazhifah Mahfuzhah; Maya Pratiwi Hutabarat; Syahira Addina; Wahyu Hayati Maser (Talenta Publisher Universitas Sumatera Utara, 2026)
This community service activity aims to apply appropriate technology, namely VGC-J300 slicing machines and high-pressure stoves, to increase production capacity, productivity, and ergonomics at Cemilan Wety in Medan. Before the intervention, the production process relied on manual equipment, particularly during the slicing stage, resulting in prolonged processing times, limited output, and high physical workloads. The implementation method involved field surveys, partner discussions, equipment procurement, hands-on training, and monitoring and evaluation. The success of the program was evaluated by comparing before- and after-intervention conditions in terms of production capacity (kg per day), time efficiency, and changes in physical workload during the production process, as assessed through observations and interviews with partners. The technological solutions provided included a VGC-J300 slicing machine and a high-pressure stove. The results demonstrated a significant increase in production capacity across all product lines: cassava chips increased by 66.67% (from 30 kg to 50 kg), and Mustofa potato (spiced matchstick potatoes) increased by 48.15% (from 22.5 kg to 33.33 kg). In addition, productivity improved, and the slicing process became faster and more consistent. Meanwhile, the frying process became more efficient through stable heat output. Furthermore, work ergonomics improved as the physical workload decreased, creating a more comfortable work environment. In conclusion, the effective application of appropriate technology has improved production efficiency, production capacity, and the quality of work processes in a sustainable manner.